Haircutting for dummies - Spear, J. Elaine (--For dummies., 2022)
"Ever wondered if you could hack it at cutting your friends' and family's hair, or could even make it as a full-blown stylist? If you've got a little creative spark-a love of crafting or painting or a talent for home makeovers-and an obsessive yen to redo the dos you see around you, it's more than likely you can make the cut. The new edition of Haircutting For Dummies shows you how to draw out your inner artist and bring your ideas to glorious life on the heads of your nearest and dearest-and will help shave dollars off your beauty budget into the bargain! In a free-spirited, chatty style, master stylist and social media corporate beauty consultant Jeryl E. Spear sits you down for a comprehensive snip-and-tell overview of how to reproduce the latest short, medium, and long hairstyles, as well as fancying things up with cutting-edge techniques like slicing, notching, and layering. Jeryl also provides a drawerful of tips on the tools you'll need to get started"--